The written English vocabulary of fourth year students in four public secondary schools in Greater Manila - Ballesteros, Jesusa D. 1932-
The nature and size of the written English vocabulary of fourth year students were determined in this study. The four high schools used in this study were: Rizal High School, Gregorio Perfecto High School, Carlos P. Garcia High School, and Elpidio Quirino High School.